Penyuluhan Hukum Tentang Sengketa Tanah di Kelurahan Cina Kabupaten Wajo - Ismail Ali; Sulaeman; Andi Wahyuddin Nur; Martono; Rusman; Tajuddin, Abdul Majid; Zahrah Salsabila (Compile Journal of Society Service, 2025)
Legal counseling on land disputes in Cina Village, Pammana District, Wajo Regency is a community service research in Field Work Lectures (KKL) as one form of implementation of the tri dharma of higher education. This counseling is carried out to increase public understanding regarding land in order to reduce or prevent the emergence of land disputes. In addition, this counseling aims to provide solutions to dispute resolutions that occur in the community that are currently happening. The counseling method is carried out by conducting initial observations on the problems that occur, followed by providing materials and discussions